Customer Satisfaction Analysis in the Healthcare Industry Using KANO Method and Importance Performance Analysis - Delima, Mira; Hanoum, Syarifa; Salahudin, Muhammad Saad (Jurnal Teknologi dan Manajemen, 2025)
Customer satisfaction is one of the most important aspects in the business world, especially in the service sector because it can increase customer loyalty, and create a positive image for the company and ultimately contribute to long-term success. This study was conducted at MEDCORP, a company engaged in the healthcare industry, which seeks to increase sales by improving customer service. To measure and customer satisfaction, this study uses 5 Dimensions of service quality, namely reliability, responsiveness, assurance, empathy and direct evidence. The methods used are the IPA and KANO methods. The IPA method uses data from customers to evaluate how important each attribute is and how well the company meets those expectations. The KANO method identifies attributes that can increase customer satisfaction if added or improved. This combination provides a more comprehensive understanding of customer needs and product performance that can be used as a reference for companies in achieving the service desired by customers, so that it can increase sales and customer satisfaction. Based on the results obtained, it is known that there are 23 negative gaps, so further analysis is carried out to determine the strategy set. The author makes three types of strategies that can be implemented, namely the main, middle, and final priority strategies based on the IPA-KANO integration classification. Through this research, it is expected to be used as a consideration for business actors or managers in determining improvements in service quality through continual improvement of MEDCORP's performance so that service quality and output become better.